Development of Digital Storybook Based on Balinese Local Culture to Enhance Cultural Citizenship Literacy and Civic Education Learning Outcomes - I Made Aditya Dharma; Made Padmarani Sudewiputri (International Journal of Elementary Education, 2025)
The limited availability of learning media that integrate local cultural values with digital technology poses challenges in supporting Cultural Literacy Citizenship and Pancasila Education in elementary schools. Existing learning media remain predominantly conventional and have not yet fully supported contextual and interactive learning. This study aimed to develop and examine the feasibility of a digital storybook based on local cultural values and to analyze its validity, practicality, and effectiveness in improving students’ learning outcomes. The research used the ADDIE development model. The research subjects included nine expert validators, teachers and students for practicality testing, and 114 fifth-grade students for effectiveness testing using a quasi-experimental design. Data were collected through expert validation instruments, response questionnaires, and learning outcome tests. Data analysis employed the Content Validity Ratio (CVR) to assess validity, descriptive analysis to evaluate practicality, and multivariate analysis (MANOVA) converted into effect size to measure effectiveness. The results indicate that the developed product is valid, practical, and effective in improving learning outcomes. The findings conclude that integrating local culture into digital learning media contributes positively to the quality of learning. The implication of this study is that teachers and media developers can adopt this approach to support the implementation of culturally responsive and innovative learning.